Dos sindicatos ao governo: a organização nacional do PT de 1980 a 2005 - Ribeiro, Pedro José Floriano (2008)
The thesis main goal was to test the partial applicability of the cartel party model (Katz and Mair), to understand the transformations in the national structure of the Workers Party (Partido dos Trabalhadores PT) between 1980 and 2005. The main hypotheses of the research derive directly from two of the three defining elements of such model. The secondary purpose was to build a general vision of the party organization during the period, focused on institutional changes, emphasizing motivations, strategies and conflicts associated to such changes. Two analytical dimensions were utilized: the functional and the organizational. On the functional dimension we detected that, during 25 years, the petista organization established a solid relationship with the state, and an estrangement from civil society. Such state links became essential for the party survival. The new situation affected the balance of power inside the party. On the organizational dimension, we observe a strengthening and greater autonomy of the party in public office , even capable to dominate the party in central office . On the other hand, the strategies of hegemonic party faction (Articulação/Campo Majoritário) shattered the intra-party democracy, increasing the importance and autonomy of the party in central office , while the party membership became less significant. The Michels iron law of oligarchy was corroborated: the Workers Party of Brazil could not escape from your oligarchization. If the party in public office and party leadership win with this new balance of power, there is only one looser: the party membership.